2021
DOI: 10.1186/s12284-021-00531-7
|View full text |Cite
|
Sign up to set email alerts
|

The Elite Alleles of OsSPL4 Regulate Grain Size and Increase Grain Yield in Rice

Abstract: Grain weight and grain number, the two important yield traits, are mainly determined by grain size and panicle architecture in rice. Herein, we report the identification and functional analysis of OsSPL4 in panicle and grain development of rice. Using CRISPR/Cas9 system, two elite alleles of OsSPL4 were obtained, which exhibited an increasing number of grains per panicle and grain size, resulting in increase of rice yield. Cytological analysis showed that OsSPL4 could regulate spikelet development by promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 79 publications
0
13
0
1
Order By: Relevance
“…The previous study has shown that the most recent whole-genome duplication in rice has led to five duplicated pairs of OsSPL genes (pair 1: OsSPL3/12; pair 2: OsSPL4/11; pair 3: OsSPL5/10; pair 4: OsSPL14/17; and pair 5: OsSPL16/18). All five OsSPL pairs are retained and exhibit partially redundant functions and evidence for neofunctionalization [5,10,13,14,31,33,37,50,69]. For example, OsSPL3 knockout altered the heading date, whereas OsSPL12 knockout did not; OsSPL4 knockout altered the heading date, whereas OsSPL11 knockout did not; OsSPL5 knockout changed the tiller number, whereas OsSPL10 knockout did not [31].…”
Section: Divergence Between Osspls and Tasplsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study has shown that the most recent whole-genome duplication in rice has led to five duplicated pairs of OsSPL genes (pair 1: OsSPL3/12; pair 2: OsSPL4/11; pair 3: OsSPL5/10; pair 4: OsSPL14/17; and pair 5: OsSPL16/18). All five OsSPL pairs are retained and exhibit partially redundant functions and evidence for neofunctionalization [5,10,13,14,31,33,37,50,69]. For example, OsSPL3 knockout altered the heading date, whereas OsSPL12 knockout did not; OsSPL4 knockout altered the heading date, whereas OsSPL11 knockout did not; OsSPL5 knockout changed the tiller number, whereas OsSPL10 knockout did not [31].…”
Section: Divergence Between Osspls and Tasplsmentioning
confidence: 99%
“…Therefore, comparisons between OsSPLs and TaSPLs, in the aspects of gene orthology, expression patterns, and functions may indicate the functions of TaSPL genes, thus helping to prioritize the TaSPL genes for detailed genetic and functional studies. To this end, we collected the known functions of OsSPL genes based on previous reports [5,6,11,13,14,[30][31][32][33][34][35][36][37]44,69] (Table S5). Consistent with the observations that most Os-SPL genes are widely expressed in several organs-including leaves, stems, inflorescences, and seeds-with expression preferences in certain tissues and stages (Figure S7), several published investigations have revealed the pleiotropic functions of OsSPLs, and the complex functional redundancy between the OsSPL members (summarized in Table S5).…”
Section: Toward Linking the Functions Between Osspls And Tasplsmentioning
confidence: 99%
“…Among the screened hub genes, the SPL gene family plays an important role in plant growth and increases crop yield by regulating the architecture of rice plants [ 63 , 64 ]. In rice, SPL4 could be a key regulator of grain size by acting on cell division control to improve rice yield and the overexpression of SPL4 decreased grain weight and size [ 65 ]. Seed-specific overexpression of SPL12 and plant Architecture 1 ( IPA1 ) enhance seed improved seed dormancy grain size in rice [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEP1 , DEP2 and DEP3 also influence grain size apart from inflorescence architecture ( Huang et al., 2009 ; Li et al., 2010 ; Qiao et al., 2011 ). Knockout of OsSPL4 or overexpression of OsSPL13 enlarges both inflorescences and grains ( Si et al., 2016 ; Hu et al., 2021b ). The loss of function of MOC1 , LAX1 , and LAX2 simultaneously reduces the number of tillers and panicle branches ( Komatsu et al., 2001 ; Li et al., 2003 ; Tabuchi et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%